2012
DOI: 10.1002/ejsp.1843
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic religiosity reduces intergroup hostility under mortality salience

Abstract: Results of three studies indicate that intrinsic religiosity and mortality salience interact to predict intergroup hostility. Study 1, conducted among 200 American Christians and Jews, reveals that under mortality salience, intrinsic (but not extrinsic or quest) religiosity is related to decreased support for aggressive counterterrorism. Study 2, conducted among 148 Muslims in Iran, demonstrates that intrinsic religiosity predicts decreased out-group derogation under mortality salience. Study 3, conducted amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 68 publications
2
15
0
1
Order By: Relevance
“…This is not to say that pre-existing religiosity does not matter. Indeed, as demonstrated in past research showing that intrinsic religiosity moderates the effects of mortality salience threats (Golec de Zavala et al, 2012;Jonas & Fischer, 2006), levels of pre-existing religiosity likely influence whether people spontaneously adhere to their religious beliefs in threatening cir cumstances when these beliefs have not been experimentally primed.…”
Section: The Role Of Pre-existing Religiositymentioning
confidence: 89%
See 4 more Smart Citations
“…This is not to say that pre-existing religiosity does not matter. Indeed, as demonstrated in past research showing that intrinsic religiosity moderates the effects of mortality salience threats (Golec de Zavala et al, 2012;Jonas & Fischer, 2006), levels of pre-existing religiosity likely influence whether people spontaneously adhere to their religious beliefs in threatening cir cumstances when these beliefs have not been experimentally primed.…”
Section: The Role Of Pre-existing Religiositymentioning
confidence: 89%
“…Some forms of religiosity are associated with prejudice toward various outgroups (Hunsberger & Jackson, 2005;Rowatt et al, 2006), a relation also observed in priming studies (Johnson, Rowatt, & LaBouff, 2010;LaBouff, Rowatt, Johnson, & Finkle, 2012). Several surveys with Palestin ians have revealed that frequency of Mosque attendance (but not frequency of prayer) predicts support for suicide attacks (Ginges et al, 2009). Further, implicitly primed religious concepts increase vengeful behavior if revenge is recommended by an authority figure (Saroglou et al, 2009), and priming vengeful religious teachings increases aggression toward a fellow participant (Bush man et al, 2007).…”
Section: Magnanimous Religion?mentioning
confidence: 94%
See 3 more Smart Citations